Near-Term Opportunities for Integrating Biomass into the U.S. Electricity Supply Technical Considerations - Ortiz, David S. (RAND Corporation, 2011)
Biomass is an increasingly important source of electricity, heat, and liquid fuel. One near-term option for using biomass to generate electricity is to cofire biomass in coal-fired electricity plants. This report focuses on two aspects of biomass use: plant-site modifications, changes in operations, and costs associated with cofiring biomass; and the logistical issues associated with delivering biomass to the plant.